Impaired spermatogenesis in the twitcher mouse: A morphological evaluation from the seminiferous tubules to epididymal transit. (4th March 2017) - Luddi, Alice; Gori, Martina; Crifasi, Laura; Marrocco, Camilla; Belmonte, Giuseppe; Costantino-Ceccarini, Elvira; Piomboni, Paola
ABSTRACT: Spermatogenesis is a complex process of proliferation and differentiation during male germ cell development whereby undifferentiated spermatogonial germ cells evolve into maturing spermatozoa. In this developmental process the interactions between different cell types are finely regulated, hence any disruption in these relationships leads to male infertility. The twitcher mouse, the murine model of Krabbe disease, is characterized by deficiency of galactosylceramidase, an enzyme also involved in the metabolism of the galactosyl-alkyl-acyl-glycerol, the precursor of sulfogalactosyl-alkyl-acyl-glycerol, the most abundant glycolipid in spermatozoa. Twitcher mice are sterile due to alterations of spermatogenesis resulting in the production of spermatozoa with abnormally swollen acrosomes and bent flagella, mainly at the midpiece–principal piece junction. The current study employs light, fluorescence, and electron microscopy to examine the defective spermiogenesis leading to the morphological abnormalities of mature sperm. This study reveals that alterations in germ cell development can be initially detected at the stage VIII and IX of spermatogenesis. The disrupted spermatogenetic process leads to a reduced number of elongating spermatids and spermatozoa in these mutant animals. Electron microscopy analysis demonstrates major acrosomal and chromatin condensation defects in the mutants. In addition, in twitcher mice, the epididymal architecture is impaired, with stereocilia of caput and corpus broken, detached and completely spread out into the lumen. These findings indicate that seminolipid expression is crucial for proper development of spermatocytes and spermatids and for their normal differentiation into mature spermatozoa. Abbreviations : GALC: galactosylceramidase; GalAAG: galactosyl-alkyl-acyl-glycerol; SGalAAG: sulfogalactosylalkylacylglycerol; PND: postnatal day; PAS: periodic acid-Schiff stain; TEM: transmission electron microscopy; SEM: scanning electron microscopy; PFA: paraformaldheyde